UMA NOVA ESPÉCIE DE ARACHNOMIMUS BRASILEIRA (ORTHÔPTERA, PHALANGOPSITIDAE) - Wiendl, Frederico M. (REVISTA DE AGRICULTURA, 2016)
UMA NOVA ESPÉCIE DE ARACHNOMIMUS BRASILEIRA (ORTHÔPTERA, PHALANGOPSITIDAE)